Wild Cherry (Prunus microcarpa) Ameliorates Azoxymethane-Induced Aberrant Crypt Foci in vivo: Depicted Molecular Mechanisms - Abduljabbar, Ahmed A.; Ismail, Parween A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2025)
Colorectal cancer is the third diagnosed cancer across the globe despite modern therapeutic interventions. Prunus microcarpa has been consumed as a therapeutic tea for several human disorders; therefore, the study investigates the chemoprotective effects of Prunus microcarpa against azoxymethane-induced aberrant crypt foci (ACF) in rats. Fifty Sprague-Dawley rats were divided into five groups: a normal control group and untreated rats given saline; a reference group treated with 5-fluorouracil; and two groups treated with 500 mg/kg methanolic extracts of fruits and stems (MEPMF and MEPMS), separately, for two months. Additionally, all rats, except the normal controls, were injected with azoxymethane twice a week for two consecutive weeks and consumed sodium dextran sulfate-mixed water for seven days. The plant extracts exhibited significant resistance against AOM-induced colon carcinogenesis, as indicated by lower ACF formation, reduced glandular dysplasia, decreased hyperchromasia, and a higher organization of simple columnar epithelial cells compared to vehicle rats. Immunohistochemical results demonstrated increased modulatory effects of MEPMF on apoptosis mediators, evidenced by higher Bax and lower PCNA levels in colonic tissues compared to MEPMS. Prunus supplementation led to decreased oxidative stress and cellular infiltrations in colon tissues, as evidenced by increased endogenous antioxidants (SOD, CAT, and GPx) and reduced inflammatory mediators (TNF-α and IL-6) and lower levels of peroxidation byproducts (MDA), while preserving organ functions such as those of the liver and kidneys. This study presents safety margin and chemoprotective effects of P. microcarpa against AOM-induced colon cytotoxicity, evidencing a viable source for nutraceutical and biopharmaceutical formulation.